Management of Avabahuka (Frozen Shoulder) With Modified Method of Agnikarma - A Single Case Study - Dr. Virani Miti,; Dr. Patel Kalapi, (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Avabahuka is one such disease that hampers the day-to-day activity of an individual. Avabahuka is considered to be a disease that affects the shoulder joint (Amsasamdhi) and it is caused due to the aggravated Vata Dosha and symptoms like pain during movement, stiffness and restricted movements of the shoulder joint. The clinical condition Avabahuka described in Ayurveda is having the similar clinical features as frozen shoulder of conventional medicine. It is found in routine Ayurvedic practice that patients of frozen shoulder do not get satisfactory relief in signs and symptoms with routine anti Vata treatment. Sushruta Samhita has mentioned that when any of the disease is not responding to conventional Ayurvedic management than it should be treated with Agnikarma. Objectives: To study the effect of Modified method of Agnikarma in the management of Avabahuka Roga (frozen shoulder). Case Summary: A 48 years old female with frozen shoulder underwent modified Agnikarma procedure using Arkapatra and flaming cotton swab hold by artery forceps. Assessments were done using VAS (Visual Analogue scale) and Grade score of stiffness. Remarkable reduction in pain and stiffness was observed within 15 days. Discussion & Conclusion: The modified Agnikarma method proved effective and safe in reducing pain and improving function in frozen shoulder. This modified technique may help standardize Agnikarma practice and enhance clinical outcomes. Conclusion: Modified method of was useful in Avabahuka.